Developing Professional Competence for Arabic Teachers Based on a Praxeological Approach: A Systematic Literature Review - Nurbayan, Yayan; Sanusi, Anwar; Wulan, Neneng Sri; Ismail, Zawawi bin (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study aims to design professional competence for Arabic language teachers in secondary schools using a praxeological approach, which focuses on three primary cycles: see, act, and judge. This study uses the Systematic Literature Review (SLR) method. In data collection, this study uses three databases, namely Google Scholar, Emerald, and ScienceDirect, which are open-access for collecting literature. Through a systematic literature review, this study explores how these three cycles can be integrated to improve the professional competence of Arabic language teachers in teaching Arabic. The results of this study indicate that the design of professional competence based on praxeology for Arabic language teachers consists of the see cycle, which has indicators: Teachers diagnose the difficulties experienced by students in expressing something using Arabic and other foreign languages. At the same time, the act cycle emphasizes the implementation of learning strategies carried out by teachers according to the results of the diagnosis of student difficulties. At this stage, teachers are required to have the ability to speak Arabic and other foreign languages (multilingual). Then. The judge cycle refers to evaluating the effectiveness of the actions that have been taken, aiming to improve and continuously develop teaching practices. Integration of this approach in teacher training programs is highly recommended to improve the standards of professional competence of Arabic language teachers in secondary schools.